Analysing African Traditional Gods Through a Trinitarian Apologetic - Ndereba, Kevin Muriithi (African Theological Journal for Church and Society, 2022)
Christian apologetics within the African continent is undergoing some level of retrieval. While classical topics such as the existence of God and the problem of evil and suffering are critical questions to answer for the emerging generations, there is a need to answer specific questions that emerge from the African religious heritage. Among them is the question of whether the Triune God of Christianity is the same as the gods of the African Traditional Religions (ATRs), and if not, what do we make of the doctrine of God in view of the two traditions? To explore this question, this article utilises a comparative approach in analysing the understanding of God in ATRs and in classic Christian trinitarianism. Beginning with an overview of the socio-cultural and worldview antecedents in African societies, this article then contrasts the doctrine of God within ATRs with the doctrine within a Christian worldview. The contribution of this article is in explicating the continuities and discontinuities between ATRs and Christian trinitarianism, and especially in formulating apologetics within the African context.
free
Keywords: ATR; African Traditional Religion; Apologetics; Doctrine of God; Trinitarianism